Epigenetic modifications of gut microbiota and their potential role in atherosclerosis - Guo, Shuang; Zhao, Junlai; Zhu, Rongrong; Fan, Zhi; Liu, Shibiao; Wu, Weiwei (Frontiers in Pharmacology, 2025)
Emerging evidence positions the gut microbiota as a pivotal regulator of host metabolism and immunity, particularly in atherosclerosis pathogenesis, with epigenetic mechanisms serving as fundamental mediators of gene expression control. This review systematically summarizes gut microbiome-driven epigenetic pathways, encompassing DNA methylation, histone modifications, non-coding RNA networks and their interplay with atherosclerosis-related pathological processes. We synthesize current evidence on microbiota-epigenome crosstalk, highlighting its potential mechanistic contributions to atherosclerotic plaque development.